Congenital Rubella Syndrome - A Major Review and Update (Delta Medical College Journal, 2015)
Rubella is a major public health problem which is usually a mild rash illness in children and adults. However, it has devastating systemic consequences when rubella virus crosses the placental barrier and infects fetal tissue resulting in congenital rubella syndrome (CRS). Congenital rubella syndrome is an under-recognized public health problem in Bangladesh and the burden of the disease weighs heavily on patients and society; therefore, routine vaccination and other preventative strategies are strongly encouraged. Extensive surveillance studies should be conducted to eliminate CRS from our country. In this review, we will characterize the epidemiology of CRS; describe the patho-phyisiology, clinical features and laboratory testing for the disease, and discuss measures needed for prevention of rubella and CRS.Delta Med Col J. Jul 2015; 3(2): 89-95